2019
DOI: 10.2460/javma.254.4.487
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of anemia and erythrocyte morphological anomalies in dogs with lymphoma or inflammatory bowel disease

Abstract: OBJECTIVE To assess the prevalences of anemia and various RBC anomalies in dogs with lymphoma versus inflammatory bowel disease (IBD) and to evaluate potential relationships between these variables and the severity of lymphoma. DESIGN Retrospective cross-sectional study. ANIMALS 82 client-owned dogs. PROCEDURES Medical records and blood smears were reviewed for dogs in which IBD or lymphoma had been diagnosed between January 1, 2006, and December 31, 2014, and for healthy dogs evaluated during that time frame.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The pathogenesis contributing to anaemia in dogs suffering from lymphoma is undetermined. However, chronic disease with associated bone marrow erythroid hypoplasia, erythrocyte decreased survival, auto‐immune hemolytic anaemia, abnormal iron reutilization, decreased erythropoietin production, and high levels of IL6 are possible contributors 51‐53 . The possible impact of anaemia on survival may come from the presence of chronic hypoxia leading to the selection of lymphoid cells which are more resistant to treatment 54 .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis contributing to anaemia in dogs suffering from lymphoma is undetermined. However, chronic disease with associated bone marrow erythroid hypoplasia, erythrocyte decreased survival, auto‐immune hemolytic anaemia, abnormal iron reutilization, decreased erythropoietin production, and high levels of IL6 are possible contributors 51‐53 . The possible impact of anaemia on survival may come from the presence of chronic hypoxia leading to the selection of lymphoid cells which are more resistant to treatment 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that diabetic ketoacidosis can cause oxidative damage to erythrocytes in cats and dogs ( 11 , 12 , 20 , 21 ). Additionally, some dogs in the present case series had inflammatory diseases (pancreatitis [Dog 3, Dog 4, and Dog 11] and pyometra [Dog 10]), which could contribute to oxidative damage, and 1 dog (Dog 4) had lymphoma, which could also cause oxidative damage ( 20 , 21 , 31 ). Since there was no correlation between the number of HBs and the dose of metamizole and because many dogs in this case series had multiple diseases/problems, the oxidative damage to erythrocytes could have been multifactorial and not only related to oxidative damage secondary to metamizole administration, at least in some dogs.…”
Section: Discussionmentioning
confidence: 95%
“…Codocytes are also known as target cells. They occur in association with liver damage, kidney disease, iron deficiency anemia, disorders of the bile ducts, and spleen ( 37 , 52 , 53 ). Spherocytes, which are small cells without a central pallor, are characteristic of hereditary spherocytosis and autoimmune hemolytic anemia ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%